2014
DOI: 10.1039/c4cc00081a
|View full text |Cite
|
Sign up to set email alerts
|

A high-performance alginate hydrogel binder for the Si/C anode of a Li-ion battery

Abstract: An alginate hydrogel binder is prepared through the cross linking effect of Na alginate with Ca(2+) ions, which leads to a remarkable improvement in the electrochemical performance of the Si/C anode of a Li-ion battery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
140
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(142 citation statements)
references
References 27 publications
1
140
0
1
Order By: Relevance
“…For instance, the calcium-mediated crosslinked alginate hydrogels and some hybridized networks have been proposed as novel binders for Si and 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 Si-based anodes. [20][21][22][23][24] Other strategies of fabricating self-healing polymer through supramolecular interactions were also adopted for Si binder. 25,26 These 3D crosslinked designs significantly improved the electrochemical performance of Si.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the calcium-mediated crosslinked alginate hydrogels and some hybridized networks have been proposed as novel binders for Si and 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 Si-based anodes. [20][21][22][23][24] Other strategies of fabricating self-healing polymer through supramolecular interactions were also adopted for Si binder. 25,26 These 3D crosslinked designs significantly improved the electrochemical performance of Si.…”
Section: Introductionmentioning
confidence: 99%
“…25 G blocks of alginate selectively couple with Ca 2+ to form a row of reversible and strong electrostatic cross-links called ''the egg-box structure'' (Fig. 25,27,28 Very recently, it was reported that Ca 2+ added alginate was used as a binder for Si-anodes. 26 The high unzipping energy of the cross-links can enhance alginate's stiffness and toughness; furthermore, re-zipping of cross-links spontaneously heals the mechanical damage to the cell wall of brown algae.…”
Section: Introductionmentioning
confidence: 99%
“…1b). 28 However, they did not study the origin of the improved performance of Ca 2+ added alginate as a binder for Si-anodes. 25,27,28 Very recently, it was reported that Ca 2+ added alginate was used as a binder for Si-anodes.…”
Section: Introductionmentioning
confidence: 99%
“…Further, the mentioned steric barrier formed by the adsorbed layer around particles prevents the coagulation as well. More interestingly, the existence of HAlg in the system can interact with the alcohols medium via the interactions between carboxyl groups and hydroxyl groups, which is favorable for dispersive uniformity by forming an organic network [32]. Bearing these in mind, ethylene glycol is much expected to be used as the medium, for it forms a much stable rheological system and owns two active hydroxyl groups per molecular.…”
Section: Effects Of the Media On Rheological Phase Reactionmentioning
confidence: 98%
“…Besides, the adsorbed molecules extend from the particle surface to the solution and exert repulsive steric force, which keeps the particles separated as well [30,31]. Form this point, HAlg as a liner hydrophilic polysaccharide with numerous carboxyl groups and hydroxyl groups makes it possible to anchor on particle surface and brings the particles with steric barrier and surface chemistry change [32]. Fig.…”
Section: Effects Of Dispersants On Ball-milling Effectivenessmentioning
confidence: 98%